2021
DOI: 10.3390/antibiotics10010068
|View full text |Cite
|
Sign up to set email alerts
|

Insects, Rodents, and Pets as Reservoirs, Vectors, and Sentinels of Antimicrobial Resistance

Abstract: This paper reviews the occurrence of antimicrobial resistance (AMR) in insects, rodents, and pets. Insects (e.g., houseflies, cockroaches), rodents (rats, mice), and pets (dogs, cats) act as reservoirs of AMR for first-line and last-resort antimicrobial agents. AMR proliferates in insects, rodents, and pets, and their skin and gut systems. Subsequently, insects, rodents, and pets act as vectors that disseminate AMR to humans via direct contact, human food contamination, and horizontal gene transfer. Thus, inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 257 publications
(205 reference statements)
0
43
0
2
Order By: Relevance
“…E. coli is a commensal microbe in humans and chickens that carries and spreads resistance genes to other pathogens [ 6 ], threatening public health. Rodents that invade human habitats carry and transmit different zoonotic pathogens including MDR E. coli, threatening human health [ 7 , 8 ]. The interaction between rodents, humans, livestock and their environment in households can facilitate sharing of antibiotic-resistant bacteria and their resistance genes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…E. coli is a commensal microbe in humans and chickens that carries and spreads resistance genes to other pathogens [ 6 ], threatening public health. Rodents that invade human habitats carry and transmit different zoonotic pathogens including MDR E. coli, threatening human health [ 7 , 8 ]. The interaction between rodents, humans, livestock and their environment in households can facilitate sharing of antibiotic-resistant bacteria and their resistance genes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, insects have been enrolled as edible products, as alternative source of energy and the high-quality protein content. It has been demonstrated that cockroaches, houseflies, ants, and mosquitoes can harbor AMR ( Gwenzi et al., 2021 ). The same worrying phenomenon has been recognized for wild insects that can share habitats with humans and can carry on AMR from environment to humans ( Gwenzi et al., 2021 ).…”
Section: Antimicrobial Resistance In Food Producing Animalsmentioning
confidence: 99%
“…Antibiotics are very often used in the clinical practice of companion animals, considering that the number of pets has been growing substantially over the last decades and people asks for the same level of care and cure expected for a family member ( Guardabassi, 2004 ; Singleton et al., 2017 ; Singleton et al., 2020 ). They represent a crucial point in the transmission of AMR through direct contact, bites, scratches, and licks and considering that they share lifestyles, habits, and spaces with their owners ( Bandyopadhyay and Samanta, 2020 ; Gwenzi et al., 2021 ; Pomba et al., 2017 ; Singleton et al., 2020 ). As previously established for other sources, also the indiscriminate use or over-usage of antibiotics over the past years has greatly enhanced the AMR, resulting in strong selective pressure with reduced sensitivity or acquisition of resistance to several antimicrobial families at the same time ( Aworh et al., 2019 ; Damborg et al., 2016 ).…”
Section: Antimicrobial Resistance In Petsmentioning
confidence: 99%
“…Znacznie rzadziej badane są natomiast inne bezkręgowce, jak np. mrówki czy pszczoły (13). W świetle doniesień z ostatnich lat, zwierzęta wolno żyjące wydają się najbardziej interesującą grupą pod względem obecności zarówno patogenów zoonotycznych, jak i specyficznych typów drobnoustrojów lekoopornych.…”
Section: Podstawowe Mechanizmy Determinujące Lekooporność W Relacjiunclassified